The complete guide to debt recovery - Mason, Roger, 1944- (London : Thorogood, 2003)
This work guides the reader through every stage of debt recovery, from deciding to take action to serving a claim and the trial itself. It deals comprehensively with enforcing judgement and features sections on bankruptcy, winding up receivership and administration.
Subtitle on cover: How to use the legal system to collect debts quickly and painlessly.
oif 06/03/15
Loan
Keywords: Collecting of accounts -- Great Britain; Debtor and creditor; Debt relief